Local Ordering Around Tetrahedral Co2+ in Silicate Glasses. Issue 1 (14th December 2013) - Hunault, Myrtille; Calas, Georges; Galoisy, Laurence; Lelong, Gérald; Newville, Matthew; Henderson, G. S.
<x xml:space="preserve">Abstract</x> Alkali lime silicate glasses containing 5 wt% of CoO were investigated by Co K‐edge XANES and EXAFS and optical absorption spectroscopy. Our results reveal the presence of tetrahedral Co2+ connected with the glass network, with a IVCo–O–Si angle of 134°. Changing the alkali from K+ to Na+ induces an increase of the local disorder around Co2+, as shown by a decrease of the contribution from the second neighbors in the EXAFS signal. We propose two models for interpreting the structure of the second shell of neighbors. Our results provide a structural basis for rationalizing the optical properties of Co2+ species in glasses.